2019
DOI: 10.18203/2394-6040.ijcmph20194503
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of postnatal depression and some associated risk factors among mothers attending the immunisation outpatient department in a tertiary health care centre: a cross sectional study

Abstract: Background: Postpartum depression is a significant and common health problem that causes a considerable amount of impact to both the mother and baby and distress on the family and society. The objective of this study is to find out prevalence of postnatal depression among mothers attending immunization outpatient department (OPD) for immunization of their baby in a tertiary health care center and to study some risk factors responsible for it.Methods: This cross sectional study was conducted in a tertiary care t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The association between PPD and income is inconsistent. 18 55 While we did not observe any association, consonant with one study, 4 some studies have observed an association. 15 30 In Indian society, the birth of a male child is preferred.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The association between PPD and income is inconsistent. 18 55 While we did not observe any association, consonant with one study, 4 some studies have observed an association. 15 30 In Indian society, the birth of a male child is preferred.…”
Section: Discussionsupporting
confidence: 81%
“…The association of PPD with age is inconsistent. Some studies did not show any association with PPD, 4 10 18 54 while some did. 3 46 Few studies have reported that increasing age heightens the probability of having PPD, particularly after 30 years.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation